Creencias irracionales en mujeres víctimas de violencia sexual de habitantes del Municipio de Florida Valle (2023)
This study investigates irrational ideas in women who have experienced sexual violence in Florida, Valle del Cauca. Given that most of the victims are women and the psychosocial impact of the ongoing crime, a bibliographic analysis of the existing literature on the subject and semi-structured interviews with five volunteers are recommended. And the interest is not pretentious either. Inappropriate psychological types do not help them to improve their quality of life and regain control over their lives. The Albert Ellis Confidence Test and the Gender Violence Survey were used as data collection tools.